Study on mechanical properties and acoustic emission characteristics of concrete-high water composites under uniaxial compression - Cao, Yue; Sun, Lei; Zhang, Xiaowu; Xu, Zhijun; Tai, Lianhai; Zheng, Yadong; Wu, Peng (Frontiers in Earth Science, 2025)
Under complex stress, a rigid filling body can easily cause the shear failure of the gob-side entry retaining (GSER) roof, and a flexible filling body can easily cause serious deformation of the roadway side. The combined filling body with a soft upper and rigid lower can respond to the needs of support strength and deformation of GSER. In this paper, the uniaxial compression test and acoustic emission (AE) characteristic test of concrete-high water composite (CHWC) specimens with different height ratios (Height ratios = High water layer height/CHWC specimens height) were performed to explore the influence of height ratio on the strength and deformation of CHWC specimens. The test results show that when the height ratio is 10% and 20%, the stress-strain characteristic curve of the CHWC specimens has secondary compaction, elastic, and plastic stages. The peak compressive strength of CHWC specimens is negatively correlated with the height of the high water layer and positively correlated with the height of the concrete layer. The peak strain of the CHWC specimens increases first and then declines with the increase of the height ratio. When the height ratio is ≤20%, the concrete layer of the CHWC specimens plays a major role in the bearing capacity. The peak strain of the CHWC specimens is about 224.4% and 348% of the uttermost strain of the pure concrete specimen (the same composition ratio of concrete). When the height ratio is ≥30%, the overall bearing structure of the CHWC specimens gradually fails after the failure and instability of the high water layer, and the concrete stratification fails to give full play to the bearing role. The research results can provide a reference for applying combined filling technology in GSER.